2011
DOI: 10.1128/jcm.01286-11
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Vibrio cholerae O1 El Tor Biotype Variant Clinical Isolates from Bangladesh and Haiti, Including a Molecular Genetic Analysis of Virulence Genes

Abstract: Vibrio cholerae serogroup O1, the causative agent of the diarrheal disease cholera, is divided into two biotypes: classical and El Tor. Both biotypes produce the major virulence factors toxin-coregulated pilus (TCP) and cholera toxin (CT). Although possessing genotypic and phenotypic differences, El Tor biotype strains displaying classical biotype traits have been reported and subsequently were dubbed El Tor variants. Of particular interest are reports of El Tor variants that produce various levels of CT, incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
114
0
9

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(129 citation statements)
references
References 46 publications
6
114
0
9
Order By: Relevance
“…We were initially interested in determining whether LT evolves into morevirulent variants over time and whether we could follow this in a set of strains isolated over 3 decades. The recent discovery of several natural variants in the LT sequence among ETEC strains isolated in Brazil (15), as well as the emergence of novel variants of the related cholera toxin (27), prompted us to evaluate the diversity of LT (LT-I) in human ETEC strains on a global scale. We identified novel LT variants and could show that both known and novel LT variants are associated with specific ETEC CF profiles, but no association with time was found.…”
Section: Discussionmentioning
confidence: 99%
“…We were initially interested in determining whether LT evolves into morevirulent variants over time and whether we could follow this in a set of strains isolated over 3 decades. The recent discovery of several natural variants in the LT sequence among ETEC strains isolated in Brazil (15), as well as the emergence of novel variants of the related cholera toxin (27), prompted us to evaluate the diversity of LT (LT-I) in human ETEC strains on a global scale. We identified novel LT variants and could show that both known and novel LT variants are associated with specific ETEC CF profiles, but no association with time was found.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical reports have revealed that the AET strains induce a more dehydrating diarrhea (22), and isolation of AET strains has been specifically associated with patients with severe diarrheal symptoms (17). Human studies have revealed a proinflammatory phase of cholera disease (23), a deviation from the traditional definition of ET cholera as "noninflammatory," although no comparative studies have been conducted.…”
mentioning
confidence: 99%
“…The tcpA gene for the major colonization factor toxin-coregulated pilus (TCP) gained the polymorphism N89S, although the functional consequence of this change is unknown (7,17). The rtxA gene for the multifunctional, autoprocessing repeats-in-toxin (MARTX) toxin acquired a stop codon (rtxA°) and the toxin became nonfunctional (18).…”
mentioning
confidence: 99%
“…The amount of CT produced was measured as described previously (32,33) during the growth of the representative strains from Zanzibar in AKI medium and compared with prototype El Tor and classical strains. It was found that all the El Tor variant strains from Zanzibar produced significantly larger amounts of CT in vitro than most strains of prototype El Tor (P Ͻ 0.001, MannWhitney U test) (Fig.…”
mentioning
confidence: 99%